The Implementation of Teaching and Learning for Islamic Education Subject (Fiqh) based on Cognitive Developmental Psychology Levels in Madrasah Tsanawiyah Negeri (MTs N) Malang 1 - Dwi Kartikawati, Rohana; ., .; ., . (International Journal of Engineering and Technology, 2018)
The object of education is human being. Undersanding student developmental psychology is essential in teaching and learning process. The research entitled â€œThe Implementation of Teaching and Learning for Islamic Education Subject (Fiqh) Based on Cognitive Developmental Psychology Levels In MTsN Malang 1â€ is intentionally aimed to explore how the teaching and learning on Islamic studies (Fiqh) could be implemented by considering the students developmental psychology.Â This is descriptive qualitative research utilizing two perspectives as theoretical bases, Islamic perspective refers to Prophet Muhammad theory, and western perspective refers to Jean Piaget and Lev Vygotsky theories. The research begins by finding the problems, then breaking theories down to be reasearch instrument and comparing it as applied in model school, MTsN Malang 1. The result, based on both Islamic and western perspective theories, shows supports. Teaching and learning process are considered to implement interactive and cooperative models. Interactive model is implemented by utilizing learning technology such as LCD-projector and computer to show audio-visual contents, quiz creator and edmodo. And cooperative model is implemented not only by learning technology, but also language development applied in mapping and presentation set. Analysis result shows that teaching and learning based on cognitive developmental levels gives more understanding for most studentsâ€™ proved by studentsâ€™ interest and excellent score. The novelty is that the research used developmental psychology which specified on cognitive to be applied in Islamic Education subject (Fiqh).Â Â